2009
DOI: 10.1002/cncr.24447
|View full text |Cite
|
Sign up to set email alerts
|

Rational approach to implementation of prostate cancer antigen 3 into clinical care

Abstract: Background Prostate cancer gene 3 (PCA3) encodes a prostate-specific messenger RNA (mRNA) that serves as the target for a novel urinary molecular assay for prostate cancer detection. Our objective is to evaluate the ability of PCA3 in addition to serum prostate-specific antigen (PSA) to predict cancer detection by extended template biopsy. Methods From September 2006 to December 2007, whole urine samples were collected after attentive digital rectal exam from 187 men prior to ultrasound-guided 12-core prosta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0
9

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(41 citation statements)
references
References 102 publications
1
31
0
9
Order By: Relevance
“…However, 12 additional studies included matched results of PCA3 and the comparators but enrolled men with both initial and repeat biopsies or they did not report biopsy history. 10,11,[35][36][37][38][39][40][41][42][43][44] Most often, the results from these studies were not stratified by biopsy history.…”
Section: Clinical Validitymentioning
confidence: 99%
See 2 more Smart Citations
“…However, 12 additional studies included matched results of PCA3 and the comparators but enrolled men with both initial and repeat biopsies or they did not report biopsy history. 10,11,[35][36][37][38][39][40][41][42][43][44] Most often, the results from these studies were not stratified by biopsy history.…”
Section: Clinical Validitymentioning
confidence: 99%
“…Fifteen studies [9][10][11]30,32,[34][35][36][37][38][39][40][41][42][43]46 reported AUC estimates for tPSA and PCA3 in the same population. Overall, 13 [9][10][11]30,32,34,35,37,38,[40][41][42]46 of the15 studies found that the AUC of PCA3 was higher than that of tPSA.…”
Section: Clinical Utilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Los estudios incluidos finalmente, tras la lectura a texto completo, fueron 14 estudios de pruebas diagnó sticas 3,7,8,[15][16][17][18][19][20][21][22][23][24][25] que cumplieron los criterios de inclusió n ( fig. 1) y un informe de una agencia de evaluació n de tecnología sanitaria elaborado por )National Horizon Scanning Centre* 26 que sintetizaba resultados varios estudios en los que en todos se obtenía buena especificidad y sensibilidad.…”
Section: Aná Lisis Descriptivo De Los Estudios Incluidosunclassified
“…En todos los trabajos se describían los criterios de selecció n de pacientes y estos eran representativos de toda la població n. El gold standard utilizado (biopsia) fue adecuado en todos los casos y este siempre era comparado con la intervenció n. En 5 artículos la realizació n de las 2 pruebas no se realizó de manera simultá nea [15][16][17]20,24 y en uno el gold standard no se aplicó a todos los pacientes 20 . El cegamiento de los investigadores para la interpretació n de la prueba de referencia solo se registró 2 estudios 7,19 .…”
Section: Calidad De Los Estudiosunclassified